Teoria da cognição judicial no processo civil - Corrêa, Leonardo Oliveira Peres (2022)
The judicial cognition theory in civil procedure is currently one of the most relevant theoretical issues in Brazilian law. Its concepts support several areas of civil procedural law, from the discovery to the executive process, in addition to provisional guardianship. The lack of studies on the theory of cognition has led to problems that are relevant to the entire discovery process, evident in the scarcity of studies on cognition in the process in theses and civil procedure manuals. The lack of such studies has affected the performance of the Brazilian judiciary, which often claims to act rationally; however, at times, this branch is known to act in an irrational and superficial manner in its concrete performance. This study focuses on the basic concepts of the theory of cognition, as well as the Brazilian Federal Constitution’s influence and the main effects of the Civil Procedure Code upon this context. We discuss three main topics: the study of the alleged difference between a matter of fact and a matter of law in civil procedure and its influence on the interpretation of judicial cognition; the study of the object of cognition (pressupositions, conditions, and merit of the process); and, lastly, the study of the cognitive plans present in the law and the application of so-called differentiated guardianship. The latter is based on the system proposed by Kazuo Watanabe of the vertical and horizontal cognitive planes. The study of the theory of cognition is fundamental to the process and especially to the improvement of the judiciary before the 2015 CPC; thus, its theoretical premises are a relevant and valuable subject of study